PENGARUH CUSTOMER VALUE TERHADAP KEMUNGKINAN PELANGGAN MENGGUNAKAN KEMBALI JASA PERBAIKAN MOBIL (PENELITIAN PADA DUTA BAN SURABAYA) (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2003)
The changes in marketplace and the challenges facing corporate marketing whereby customers will need to be convinced about product or services and corporate credibility. This shift request marketer move towards value based marketing, a concept that been convinced the value will give to the customer better than the competitor had given. Because of that, customer value becomes more popular among marketer, nowadays. Customer value is a customer perception about the benefit that they have received compare to the cost that they have spent, in order to get a products or services. There were some measurements technics to know about customer value, but this research decided to use benefit minus cost approach, which measure customer value by find a gap between benefit minus cost. The purpose of this research is to prove the causal relationship between customer value that implied on product value, service value, personal value, and image value, to the customer probability to reuse car services at Dula Ban Surabaya. This research chose Duta Ban Surabaya, as a place where this research was done. Samples of this research are Duta Ban customer's which are chosen by random sampling method. This research determines samples criteria, that is samples must be an individual customers (not corporate customers), and had used car services at Duta Ban not less than twice a year in the past of one year (July 2001 to July 2002). The objects of this research are customer perception about benefit, customer perception about cost, and probability to reuse car services at Duta Ban. Hypothesis are tested by a Linier Multiple Regression, using program software SPSS version 10.00. Inferential statistics is used to test hypothesis by t- test and F- test, at a = 0,05 level of significance at one tailed test. The result of this research confirms that hypothesis of this research are accepted. There is a positive causal relationship between customer value that implied at product value, service value, personal value, and image value and customer probability to reuse car services at Duta Ban. Among the fourth value determinant, the image value have been a relative bigger impact to the customer probability to reuse car services at Duta Ban other than the other value determinant. The result of this research also shows that, a bigger customer value, a higher customer probability to reuse car services.